Achilles Tendons Hypertrophy in Response to High Loading Training. (December 2014) - Milgrom, Yael; Milgrom, Charles; Altaras, Talya; Globus, Opher; Zeltzer, Ehud; Finestone, Aharon S.
Background: Whether the human Achilles tendon undergoes hypertrophic changes as measured by an increase in cross-sectional area, in response to endurance training exercise remains in question. We investigated the hypothesis that transition from civilian life through 6 months of elite infantry training would induce adaptive Achilles tendon hypertrophy. Methods: Seventy-two new elite infantry recruits had the cross-sectional area of their Achilles tendons measured at a point 2.5 cm proximal to the Achilles insertion by ultrasound before beginning elite infantry training. Measurements were repeated by the same ultrasonographer for those recruits who were still in the training program at 6 months. Prior to beginning the study the intraobserver reliability of the ultrasonographer's Achilles tendon measurements was calculated (intraclass correlation coefficient = .96). Fifty-five recruits completed 6 months of training. Results: The mean cross-sectional area of their right Achilles tendon increased from 47.0 ± 11.2 to 50.2 ± 9.6 mm 2 ( P = .037) and the left Achilles tendon from 47.2 ± 8.9 to 51.1 ± 8.3 mm 2 ( P = .013). The change in cross-sectional area did not correlate with subject height, weight, prior sport history, or jumping and running abilities. Conclusions: An abrupt stimulus of 6 months of elite infantry training was adequate to induce hypertrophic changes in the Achilles tendon. This is the first human prospective study showing an increase in the Achilles tendon cross-sectional area in response to rigorous endurance type training. The finding supports the hypothesis that the Achilles tendon in response to sufficiently high and sustained loading can remodel its morphological properties and thereby strengthen itself. Level of Evidence: Level II, etiology study.